The International Jewish Labor Bund after 1945 : Toward a Global History - Slucki, David, 1984- (Book collections on Project MUSE., 2012)
The International Jewish Labor Bund after 1945 charts the efforts of the surviving remnants of the movement to salvage something from the wreckage. Covering both the Bundists who stayed in communist Eastern Europe and those who emigrated to the United States, France, Australia, and Israel, the book explores the common challenges they faced.